Current redistribution during inhomogeneous quench of 2G HTS tapes. (1st September 2022) - Zampa, Alexandre; Lacroix, Christian; Badel, Arnaud; Sirois, Frédéric; Tixador, Pascal
Abstract: Inhomogeneous temperature elevations, also called hot spots, occurring in second generation high-temperature superconductor (2G HTS) tapes may lead to their destruction. A better understanding of inhomogeneous quenches would contribute to develop strategies to better protect superconducting devices based on 2G HTS tapes against hot spots. To do so, we investigated the current redistribution around a dissipative zone in a 2G HTS tape with a combination of experiments and numerical simulations based on the finite element method (FEM). Firstly, the inhomogeneous heat generation in a commercial 2G HTS bare tape (without copper cladding) was observed through the visualization of bubble generation. Secondly, the current redistribution around a dissipative zone in commercial 2G HTS bare tapes from two different manufacturers was investigated using voltage taps on both sides of the tape. The measured voltages showed that the current redistribution around the dissipative area in the top stabilizer layer of the tape is different from that in the bottom stabilizer layer. Using a 3D electro-thermal FEM model, we reproduced these behaviors, assuming a HTS tape architecture with an inhomogeneous local critical current density. Finally, using the same FEM model, we explored the impact of a lack of silver on one lateral side of a 2G HTS tape. Our results indicate that such a lack of silver does not critically affect the quench dynamics.